Recession Prediction with Optimal Use of Leading Indicators - Heikki Kauppi (Aboa Centre for Economics (ACE), 2019)
We use the gradient boosting estimation technique and the ROC curveto non-parametrically measure and exploit the maximal predictive powerof leading indicators for the future state of the business cycle. We de-velop novel procedures for finding the best performing transformationsof individual indicators, for combining them to form an optimal reces-sion prediction model and for assessing which predictors are contribut-ing in the model. Among our empirical findings with US data are thatthe predictive impact of various indicators is non-monotone and thatrecession predictions based on our nonparametric procedures clearlyoutperform the ones based on a conventional probit model.
Keywords: C22; C25; C53; E37; 330; gradient boosting; leading indicators; non-parametric esti-mation; optimal binary prediction; recession prediction